Exploration of New Operational Models and Technologies for the Synergistic Development of Deep-Sea Mining and Carbon Sequestration - Xuguang Chen; Xian Zhang; Ning Ma; Xixi Liu; Anqi Xie; Fengpeng Zhang; Rui Lyu (中国工程科学)
The ocean harbors abundant solid minerals and is the world’s largest carbon sink with vast carbon sequestration potentials. Exploring the synergistic development of deep-sea mining and carbon sequestration is of significant importance for supporting China’s green and low-carbon transformation in deep-sea mining, as well as enhancing its influence in the field of ocean development and governance. This study summarizes the development status and trends of deep-sea mining operational models, focusing on the efficient, green, and low-carbon development of deep-sea mineral resources. It proposes synergistic operations that integrate deep-sea mining with marine carbon sequestration, creating a dual-industry collaborative development model. From the perspectives of feasibility, synergy, and economic viability, the competitiveness of a "deep-sea mining + carbon sequestration" model is analyzed. Breakthrough directions and technology development pathways are proposed, including efficient integration of deep-sea mining and carbon sequestration systems, environmental impact monitoring, carbon footprint tracing, and collaborative operation equipment. Research findings indicate that CO2 jets in deep-sea mining environments exhibit a collection performance comparable to water jets, along with better environmental friendliness and lower risks of carbon sequestration leakage. Deep-sea mining and marine carbon sequestration show high complementarity in terms of operational equipment and space, with no interference in their operational cycles. This industrial collaborative development model can improve the profitability of both marine carbon sequestration and deep-sea mining. To promote the synergistic development of these two industries, it is essential to accelerate breakthroughs in core deep-sea technologies and equipment, establish a complete industrial chain and clusters, and foster the comprehensive development of compound talent teams, technical equipment, and economic benefits in deep-sea mining and marine carbon sequestration.